The influence of light on elasmobranch behavior and physiology: a review - Carroll, Daire; Harvey-Carroll, Jessica (Frontiers in Marine Science, 2023)
In this review, we summarize the state of knowledge of the influence of light on the activity and physiology of elasmobranchs (sharks, skates, rays, and sawfish). These are a diverse group with great economic and ecological importance. The long-term success of a species is largely determined by its ability to respond to changes in its environment. Light plays an important role for many marine species in signaling rhythmic environmental changes which are part of daily and annual cycles. Behavioral and physiological changes by organisms in response to these signals have evolved enabling them to maximize survival and reproductive success. In an environment with increased levels of artificial light at night (ALAN), deleterious changes in activity and physiology can occur. By summarizing what is known about the influence of light on elasmobranch activity, it can be concluded that ALAN is likely to have a negative impact on elasmobranchs at the individual and population level. We also discuss the example of intentional nocturnal light pooling by the tourism industry to attract whale sharks (Rhincodon typus) and manta rays (Mobula spp.) and recommend regulation of this activity.